1998
DOI: 10.1091/mbc.9.3.561
|View full text |Cite
|
Sign up to set email alerts
|

The Ras/Rac1/Cdc42/SEK/JNK/c-Jun Cascade Is a Key Pathway by Which Agonists Stimulate DNA Synthesis in Primary Cultures of Rat Hepatocytes

Abstract: The ability of signaling via the JNK (c-Jun NH2-terminal kinase)/stress-activated protein kinase cascade to stimulate or inhibit DNA synthesis in primary cultures of adult rat hepatocytes was examined. Treatment of hepatocytes with media containing hyperosmotic glucose (75 mM final), tumor necrosis factor α (TNFα, 1 ng/ml final), and hepatocyte growth factor (HGF, 1 ng/ml final) caused activation of JNK1. Glucose, TNFα, or HGF treatments increased phosphorylation of c-Jun at serine 63 in the transactivation do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 57 publications
(68 reference statements)
7
112
0
1
Order By: Relevance
“…Although dominant-negative PI3K did not inhibit DNA synthesis in hepatocytes, other data suggested that the cascade inhibition could abolish or only delay entry to S phase. 17,19,37 Our study clearly shows that the PI3K inhibitor, LY294002, and the FRAP/mTOR inhibitor, rapamycin, do not delay entry to S phase and expression of cyclin D1 but totally abolish DNA replication and the cyclin induction in growth factor-stimulated hepatocytes. Uncoupling of mRNA and protein levels has been pointed out in hepatocytes, suggesting that cyclin D1 is subject to control on a translation level and/or protein stability in rat liver.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although dominant-negative PI3K did not inhibit DNA synthesis in hepatocytes, other data suggested that the cascade inhibition could abolish or only delay entry to S phase. 17,19,37 Our study clearly shows that the PI3K inhibitor, LY294002, and the FRAP/mTOR inhibitor, rapamycin, do not delay entry to S phase and expression of cyclin D1 but totally abolish DNA replication and the cyclin induction in growth factor-stimulated hepatocytes. Uncoupling of mRNA and protein levels has been pointed out in hepatocytes, suggesting that cyclin D1 is subject to control on a translation level and/or protein stability in rat liver.…”
Section: Discussionmentioning
confidence: 66%
“…Concerning PI3K, few studies have been performed on hepatocytes, and those studies had conflicting results. [17][18][19][20] In this report, we analyzed the possible role of the PI3K pathway in the regulation of EGF-induced DNA replication and survival in mid-late G1 phase. We examined the relation that could exist between this pathway and the expression of cyclin D1, a critical player in G1/S transition, and questioned the interference that could exist between the PI3K and MEK/ERK pathways.…”
mentioning
confidence: 99%
“…41 The finding that mrp1 induction in cultured hepatocytes takes place at the mid G 1 -phase of the cell cycle 42 further supports our finding, because cytokines such as TNF-␣ and interleukin-6 are known to initiate a proliferation trigger in hepatocytes in vivo. [43][44][45][46] We hypothesize that ABC-transporters like MDR1 and MRP1 and their rodent homologues function as an aspecific protection system to maintain cellular membrane integrity by extruding cytotoxic compounds such as lipid peroxidation products. Furthermore, MRP1/mrp1 may contribute to the regulation of the intracellular redox state by transporting glutathione disulfide.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SEK results in the phosphorylation and activation of JNK (Sanchez et al, 1994;Auer et al, 1998;Wang et al, 1999a). The effect of UV irradiation-induced hyperactivity of K + channel on SEK activation is observed by measuring the phosphorylation status of SEK.…”
Section: Uv Irradiation-induced K + Channel and Sek Activationmentioning
confidence: 99%